Knowledge and Confidence Level among Emergency Healthcare Workers in Airway Management and Resuscitation of Suspected Covid-19 Patients: A Cross-Sectional Study in Penang and Kelantan - Md Noh, Abu Yazid; Ali, Muhammad Naeem; Mafauzy, Mohamad Masykurin; Baharuddin, Kamarul Aryffin; Goh , Swee Heng; Wan Mohamad, Wan Syahmi (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: COVID-19 cases in Malaysia have followed a never-ending course of spike and fall since it was first detected. Though the prominent role of infection control standard precautions were strictly applied, cases among emergency healthcare workers (EHCW) contracting the disease continue to rise. Our study aims to evaluate the knowledge and confidence level and the factors that may influence the knowledge and confidence level among EHCW in airway management and resuscitation of suspected COVID-19 patients. MATERIALS AND METHODS: This was a cross-sectional study conducted in tertiary hospitals in Penang and Kelantan using a validated questionnaire. The territories evaluated include the possible method of transmission, proper steps during resuscitation, airway management and intubation, intensive care management, and etiquette of personal protective equipment. RESULTS: Out of 543 EHCW eligible for the study, only 300 participants responded to the questionnaire. Our study showed only 15.3% of respondents had good knowledge and 62.3% had high confidence in airway management and resuscitation of suspected COVID-19 patients. Significant associations were seen in knowledge and confidence level among respondents with previous experience attending continuing medical education (F=7.041, P=0.008 and F=19.398, P<0.001 respectively). Significant associations were also demonstrated in confidence level among respondents with previous simulation training experience (F=13.905, P<0.001). CONCLUSION: Our study revealed that most EHCW had poor knowledge and moderately adequate confidence in the airway management and resuscitation of suspected COVID-19 patients. A more comprehensive and strategized training program needs to be conducted to help in improvement of the knowledge and confidence level among EHCW.